Application of Cu(I)-catalyzed azide–alkyne cycloaddition for the design and synthesis of sequence specific probes targeting double-stranded DNA - Vasilyeva, Svetlana V.; Filichev, Vyacheslav V.; Boutorine, Alexandre S. (Beilstein Journal of Organic Chemistry, 2016)
Efficient protocols based on Cu(I)-catalyzed azide–alkyne cycloaddition were developed for the synthesis of conjugates of pyrrole–imidazole polyamide minor groove binders (MGB) with fluorophores and with triplex-forming oligonucleotides (TFOs). Diverse bifunctional linkers were synthesized and used for the insertion of terminal azides or alkynes into TFOs and MGBs. The formation of stable triple helices by TFO-MGB conjugates was evaluated by gel-shift experiments. The presence of MGB in these conjugates did not affect the binding parameters (affinity and triplex stability) of the parent TFOs.
Keywords: binding affinity; click chemistry; Cu(I)-catalyzed azide–alkyne cycloaddition; pyrrole–imidazole polyamides; sequence specificity: DNA; triplex-forming oligonucleotides